The Recent Trend in the Use of Multistrain Probiotics in Livestock Production: An Overview - Lambo, Modinat Tolani; Chang, Xiaofeng; Liu, Dasen (Animals (Basel), 2021)
It has been established that introducing feed additives to livestock, either nutritional or non-nutritional, is beneficial in manipulating the microbial ecosystem to maintain a balance in the gut microbes and thereby improving nutrient utilization, productivity, and health status of animals. Probiotic use has gained popularity in the livestock industry, especially since antimicrobial growth promoter’s use has been restricted due to the challenge of antibiotic resistance in both animals and consumers of animal products. Their usage has been linked to intestinal microbial balance and improved performance in administered animals. Even though monostrain probiotics could be beneficial, multistrain probiotics containing two or more species or strains have gained considerable attention. Combining different strains has presumably achieved several health benefits over single strains due to individual isolates’ addition and positive synergistic adhesion effects on animal health and performance. However, there has been inconsistency in the effects of the probiotic complexes in literature. This review discusses multistrain probiotics, summarizes selected literature on their effects on ruminants, poultry, and swine productivity and the various modes by which they function.